Pengembangan Sistem Informasi Absensi Berbasis Web Menggunakan QR-Code - Aldo, Hendrikus Fiki; Koriaty, Sri; Oktarika, Dini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Attendance is an important aspect of attendance management, both in academic and corporate environments. Conventional attendance systems that still use manual signatures or identity cards often face obstacles such as data falsification, inefficiency, and difficulties in recapitulating attendance. Therefore, this research develops a web-based attendance information system using QR-Code technology as a solution that is more efficient, accurate, and secure. The research method used in this research is Research and Development (R&D), which is a research method that aims to develop a product and test its effectiveness in achieving the expected goals. This research process consists of two main stages, namely product development and product validation. Users simply scan the unique QR-Code generated by the system using a mobile device to automatically record their attendance. The test results show that this system is able to increase the efficiency of attendance recording, reduce the risk of fraud, and simplify the data recapitulation process. Thus, this QR-Code-based attendance system can be a more modern and effective alternative in attendance management